Phaeohyphomycosis caused by Phialophora americana with CARD9 mutation and 20‐year literature review in China. Issue 10 (23rd July 2019) - Huang, Chen; Zhang, Yi; Song, Yinggai; Wan, Zhe; Wang, Xiaowen; Li, Ruoyu
Summary: Background: Phaeohyphomycosis is a chronic cutaneous, subcutaneous or systemic mycotic infection caused by various dematiaceous fungi. The diverse clinical manifestations and poor prognosis of phaeohyphomycosis necessitate studies on it to better recognise the disease and improve its management. Objectives: To investigate the epidemiology, aetiology, diagnosis, treatment and prognosis of phaeohyphomycosis in China over the past 20 years, and to study the first case of phaeohyphomycosis caused by Phialophora americana and the genetic and immunological mechanisms. Patients/Methods: Clinical and laboratory findings of the case were studied, and the patient's DNA was sequenced for CARD9, followed by immunological studies using patient's PBMCs. Cases of phaeohyphomycosis in China from 1998 to 2018 in both the Chinese and English literature were collected and analysed, including 45 articles and 46 patients. Results: We confirmed the patient holding a homozygous frameshift mutation of CARD9, which led to impairment of pro‐inflammatory cytokine production, and lower Th17‐ and Th22‐associated responses upon fungus‐specific stimulation. From the literature review, we revealed that the clinical presentations of phaeohyphomycosis were diverse. Diagnoses were established mainly on the basis of histopathology and fungal culture. Oral itraconazole, voriconazole, and posaconazole are the first choices for treatment, and a combination with surgical excision is also recommended. Conclusions: Our study establishes that obtaining detailed histories is vital for understanding the immune state and that patients with recurrent or chronic phaeohyphomycosis in the absence of known immunodeficiencies should be tested for CARD9 mutations. We hope our findings will aid clinicians in the diagnoses and treatment of such infections.